PENGARUH KEJELASAN SASARAN ANGGARAN, AUDIT KINERJA DAN PERAN PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Ni Putu Devi Anggreni; Ni Komang Sumadi; Rai Dwi Andayani W (UNHI Press, 2021)
Accountability is a performance control tool in an organization. Accountability.is needed as an .that.the.implementation.of.village.government has been carried out well. Accountability can be influenced by several factors such as clarity of budget targets, performance audits and the role of village officials. This study aims to determine the effect of clarity of budget targets, performance audits and the role of village officials on the accountability of village fund management in Penebel District, Tabanan Regency. This research was conducted with a survey method using a questionnaire instrument. The number of samples studied was 90 respondents using purposive sampling technique using criteria. The results of hypothesis testing show that the variables of clarity of budget targets and the role of village officials have an effect on the accountability of village fund management and performance audits have no effect on the accountability of village fund management in Penebel District, Tabanan Regency.